Hiperactividad y su impacto en el proceso de aprendizaje de los niños de Inicial I - Rivadeneira Coello, Joselyn Nohelia (2024)
This case study focuses on analyzing hyperactivity and its impact on the learning process of preschool children. This research seeks to comprehensively understand how the presence of hyperactivity can affect children's academic performance and educational experiences at this crucial stage of development. The documentary phase immerses itself in an exhaustive review of scientific and documentary literature, examining exploratory and descriptive studies to establish a solid theoretical foundation on hyperactivity in childhood. Subsequently, the field phase focuses on data collection through academic assessments, direct observations in the school environment, and interviews with teachers. The sample includes children diagnosed with hyperactivity and a control group without said diagnosis, thus allowing us to compare and contrast academic performance, observed behaviors and perceptions of the various actors involved. The data analysis, both quantitative and qualitative, aims to shed light on the possible impacts of hyperactivity on learning and provide valuable information for decision-making in the care and education of these children. This study will not only contribute to the academic understanding of the intersection between hyperactivity and learning at the Initial Level 1 stage, but will also seek to offer practical recommendations for educators, parents and health professionals, thus promoting a more effective and comprehensive in the management of hyperactivity in educational settings.